Development of Edible Packaging Film from Whey Protein Phospholipid Concentrate - Santoso, Teguh (Auckland University of Technology, 2022)
In an attempt to utilise the natural fat content in whey protein phospholipid concentrate (WPPC), this study formulated, optimised, characterised, and compared edible films made from WPPC with films made from whey protein concentrate (WPC) and whey protein isolate (WPI). The formulation and processing utilised techniques that are considered generally safe for consumption. It was possible to produce a WPPC film using 16% (w/w) WPPC solution and glycerol at a 2:1 WPPC:GLY ratio. In terms of appearance and transparency, all films had good transparency with greater than 50% transparency at 600 nm. WPPC and WPC film were also good at blocking the UV wavelength. The WPPC and WPC films were yellow, while the WPI film was opaque/colourless. Out of the three films, the WPI film had the best appearance. As for the films’ mechanical properties, WPPC films had significantly lower tensile strength and elongation at break than the WPC and WPI films. In addition, WPPC films were very brittle compared to the WPC and WPI films. The water barrier properties of the films were interesting. WPPC films retained more water in the film matrix and performed better as a water barrier, as demonstrated by the swelling index and water vapour permeability (WVP) values, which were lower for WPPC films than WPC and WPI films. The higher moisture content, lower swelling index, and WVP suggest that either fat (phospholipid) or lactose influences the interaction between WPPC film and water and should be investigated further. Based on the film’s characteristics, the best film was from WPI. WPPC films are not practical with the current formulation and processing techniques.
Keywords: Edible packaging material; Edible film; Protein films; Whey protein phospholipid concentrate; Physical properties; Water vapour permeability